Envisioning public scholarship for our time : models for higher education researchers - Kezar, Adrianna J.; Drivalas, Yianna; Kitchen, Joseph (Excellent teacher series., 2018)
"This book proposes a new paradigm of public scholarship for our time, one that shifts from the notion of the public intellectual to the model of the engaged scholar. The editors' premise is that the work of public scholarship should be driven by a commitment to supporting a diverse democracy and promoting equity and social justice. The contributors to this volume present models that eschew the top-down framing of policy to advocate for practice that drives bottom-up change by arming the widest range of stakeholders -- especially members of marginalized communities -- with relevant research. They demonstrate how public scholarship in higher education can increase its impact on practice and policy and compellingly argue that public scholarship should be recognized as normative practice for all scholars and indeed integrated into the curriculum of graduate courses"--